Advances of Nanozyme-Driven Multimodal Sensing Strategies in Point-of-Care Testing - Ziyi Chang; Qingjie Fu; Mengke Wang; Demin Duan (Biosensors)
Point-of-care testing (POCT) has garnered widespread attention due to its rapid, convenient, and efficient detection capabilities, particularly playing an increasingly pivotal role in medical diagnostics and significantly improving the efficiency and quality of healthcare services. Nanozymes, as novel enzyme-mimicking materials, have emerged as a research hotspot owing to their superior catalytic performance, low cost, and robust stability. This review provides a systematic overview of the fundamental characteristics and classifications of nanozymes, along with various sensing strategies employed in POCT applications, colorimetric, electrochemical, fluorescent, chemiluminescent, and surface-enhanced Raman scattering (SERS)-based approaches. Furthermore, this review highlights innovative designs that enhance the sensitivity and accuracy of POCT across multiple domains, such as biomarker detection, environmental monitoring, and food safety analysis, thereby offering novel perspectives for the practical implementation of nanozymes in point-of-care diagnostics. Finally, this review analyzes current challenges in nanozyme-based POCT systems, including limitations in optimizing catalytic activity, ensuring nanozyme homogeneity, and achieving large-scale production, while proposing future development trajectories.